Evaluation of tempering influence in aisi 4340 steel hardness and microstructure - Ladeira, Dayanni Gonçalves (2017)
AISI 4340 steel is widely used in aeroespace, automotive and nuclear industries (BHATTACHARYA, 2011). It is classified as a high strength steel due to its great yield  and tensile strength (approximately 800 MPa and 1200 MPa, respectively).The objective of this work is to evaluate the influence of tempering parameters in this alloy. Samples were quenched using same temperature and keeping time. Then they were tempered using different tempering temperatures and keeping time. The influence of heat treatment in the samples were evaluated by Rockwell C hardness test and metallographic analysis.